Navigating High-Risk Obstetric Anesthesia: Successful Management of Cesarean Section with Graded Epidural Blockade in a Parturient with Atrial Septal Defect and Moderate Pulmonary Hypertension - Viky Wicaksana; Septian Adi Permana; Bambang Novianto Putro (HM Publisher, 2025)
Introduction: The convergence of a large, uncorrected atrial septal defect (ASD) with secondary pulmonary hypertension (PH) in pregnancy creates a high-risk hemodynamic environment. The physiological stresses of parturition can precipitate cardiovascular collapse. Anesthetic management for cesarean delivery must be meticulously planned to preserve the delicate balance between systemic and pulmonary vascular resistance, with the primary goal of maintaining systemic vascular resistance to prevent exacerbation of the intracardiac shunt. Case presentation: We present the case of a 28-year-old primigravida at 37+2 weeks' gestation with a known large secundum ASD and moderate PH (echocardiographically estimated sPAP of 50.2 mmHg), who required an emergency cesarean section. A comprehensive, multidisciplinary plan was formulated, prioritizing maternal hemodynamic stability. The patient was successfully managed with a carefully titrated, graded lumbar epidural anesthetic using 0.5% levobupivacaine. Advanced invasive monitoring, including arterial and central venous catheters, guided the slow induction of a T6 sensory block. This strategy resulted in hemodynamic parameters being maintained within a clinically acceptable range, obviating the need for vasopressor support. The postoperative course in the cardiovascular ICU was uneventful. Conclusion: This case provides compelling evidence that a graded epidural blockade, executed with vigilance and supported by a robust, team-based safety framework, is a highly effective anesthetic technique for cesarean delivery in parturients with ASD and moderate PH. The ability to exert temporal control over the onset of sympathetic blockade is paramount to preventing abrupt hemodynamic shifts, thereby protecting the vulnerable right ventricle and ensuring maternal safety.